Rotor-Pole Number Analysis of Double Stator PM-FSM Using 2D FEA For Optimal Output Performances - Mohd Dzubaidi, Mohamad Zakwan; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2022)
Recently, most reported research on Flux Switching Motor (FSM) are focused on Single Stator Permanent Magnet (PM) FSM topology in which the excitation sources of PMs and armature coils are accommodated at the stator. Then, there is reported research on double-stator 6Slot-7Pole configuration and shows good improvement in the output performances. However, no slot-pole number analysis has been carried out to perform the best motor configuration for optimal output performances. Thus, in this project, 12Slot-10Pole and 12Slot-14Pole DS-PMFSM analysis is carried out and then compared with 6Slot-7Pole. The analyses are implemented based on two-dimensional (2D) finite element analysis (FEA) which uses JMAG-Designer software. The concerned performance parameters are motor flux linkage, cogging torque back-emf, flux distribution, output torque and power. The results obtained show that 12Slot-14Pole DS-PMFSM gets the better result for cogging torque which is 1.076Nm, output torque at 36.8116Nm, back-emf at 2.434, flux linkage, and flux distribution than the results for 12Slot-14Pole DS-PMFSM for cogging torque which is 2.999Nm, output torque at 5.484Nm, back-emf at 2.252, flux linkage, and flux distribution. Thus, it is concluded that the investigation for slot-pole number had successfully performed the best configuration of the motor.